PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE BERMAIN PERAN SISWA KELAS V SD NEGERI 05 GURUNG - Wibowo, Dwi Cahyadi; Suryadi, Tedi; Rusdi, Rusdi; Firda, Margareta (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe speaking skills in fifth grade elementary school students using the role playing method. This research conducted by qualitative approach through classroom action research. The subjects in this research were fifth grade students at SD Negeri 05 Gurung. Data collection uses observation and interview techniques. The data analysis techniques used are data reduction, data display, and drawing/conclusions. The results of the research stated that speaking skills with the aspects assessed in the test, namely aspects of pronunciation, intonation and vocabulary, after applying the role-playing method in thematic learning increased by an average of 16.7 points from the average in cycle I of 68.3 to 85 at the end cycle II. These results also indicate an increase of 40% in learning completion from 60% of students who completed in cycle I to 100% completion in cycle II. So the use of the role playing method is very suitable as a learning method. Students also responded in the very good category to the use of role playing methods in thematic learning. Thus, the role playing method is able to improve speaking skills in fifth grade elementary school students, and is recommended for use in learning speaking skills.